Monsters on the run - Sherry, Kevin (Sherry, Kevin. Yeti files., 2015)
Yeti Blizz Richards and his gang of cryptids set out to find a friend for Vanessa, the Loch Ness Monster, even though it means traveling back in time to the dangerous age of the Cretaceous looking for plesiosaurs--unfortunately Vanessa proves to be rather timid about meeting other dinosaurs.